(untitled) (Indonesian Journal of Science and Technology, 2025)
Over recent decades, environmental degradation has escalated, negatively impacting both the planet and humanity. Numerous studies have shown that this degradation is largely driven by human activities. A key strategy to address climate change and environmental damage is to promote changes in human behavior toward more sustainable environmental management practices. One effective approach, particularly in higher education, is the integration of eco-friendly curricula and technologies. This study aims to assess student awareness and the implementation of eco-friendly curriculum and technologies in Indonesian higher education, using a case study on environmental challenges. The findings indicate that while students possess some understanding of environmental issues, such as climate change and waste, their overall awareness and involvement remain low. This is largely due to the insufficient coverage of environmental topics within the university curriculum. Additionally, practices such as waste management and the provision of sustainable technologies, like drinking water systems, are still minimal on campuses. These results underscore the critical need for governments to prioritize the inclusion of environmental concerns and sustainable practices in university curriculum and campus operations. By doing so, a greater emphasis on environmental stewardship can be cultivated, leading to increased awareness and proactive engagement in environmental protection among students.